The role of excess charge mitigation in electromagnetic hygiene: An integrative review - Isaac A. Jamieson; J. Nigel B. Bell; Paul Holdstock (Biomedical Journal)
The electromagnetic characteristics of many environments have changed significantly in recent decades. This is in large part due to the increased presence of equipment that emits electromagnetic radiation and materials that may often readily gain excess charge. The presence of excess charge can often increase the risk of infection from pathogens and the likelihood of individuals experiencing compromised performance, respiratory problems, and other adverse health issues from increased uptake of particulate matter. It is proposed that adopting improved electromagnetic hygiene measures, including optimized humidity levels, to reduce the presence of inappropriate levels of electric charge can help reduce the likelihood of ill health, infection, and poor performance arising from contaminant inhalation and deposition, plus reduce the likelihood of medical devices and other electronic devices getting damaged and/or having their data compromised. It is suggested that such measures should be more widely adopted within clinical practice guidelines and water, sanitation, and hygiene programs.